Obtention of viable cell suspensions from breast cancer tumor biopsies for 3D chromatin conformation and single-cell transcriptome analysis - Stephenson-Gussinye, Aura; Rendón-Bautista, Luis A.; Ruiz-Medina, Blanca E.; Blanco-Olais, Eduardo; Pérez-Molina, Rosario; Marcial-Medina, Cleofas; Chavarri-Guerra, Yanin; Soto-Pérez-de-Celis, Enrique; Morales-Alfaro, Andrea; Esquivel-López, Ayerim; Candanedo-González, Fernando; Gamboa-Domínguez, Armando; et al. (Frontiers in Molecular Biosciences, 2024)
Molecular and cellular characterization of tumors is essential due to the complex and heterogeneous nature of cancer. In recent decades, many bioinformatic tools and experimental techniques have been developed to achieve personalized characterization of tumors. However, sample handling continues to be a major challenge as limitations such as prior treatments before sample acquisition, the amount of tissue obtained, transportation, or the inability to process fresh samples pose a challenge for experimental strategies that require viable cell suspensions. Here, we present an optimized protocol that allows the recovery of highly viable cell suspensions from breast cancer primary tumor biopsies. Using these cell suspensions we have successfully characterized genome architecture through Hi-C. Also, we have evaluated single-cell gene expression and the tumor cellular microenvironment through single-cell RNAseq. Both technologies are key in the detailed and personalized molecular characterization of tumor samples. The protocol described here is a cost-effective alternative to obtain viable cell suspensions from biopsies simply and efficiently.pg.